Development of a Textbook in the Modern Educational and Scientific Mathematical and Informatics Environment of Higher Education Students - Marianna Kovtoniuk; Olena Soіa; Olena Kosovets; Ivanna Leonova (Proceedings of the International Conference on Applied Innovations in IT)
The article deals with the problems of modelling and functioning of a textbook (digital textbook) as an integral part of the educational and scientific mathematical and informatics environment of higher education. It is shown that a high-quality digital textbook ensures the formation of not only the mathematical culture of a future specialist, but also the formation of such basic competencies as the ability and willingness to self-learn, apply knowledge, skills and abilities to work with computer mathematics systems to improve the efficiency of education, self-education and professional activity. The features of a modern digital textbook in mathematical disciplines in the preparation of a bachelor of mathematics are discussed: 1) the theoretical aspect of creating textbooks in the educational space of a bachelor of mathematics in the conditions of blended learning in Ukraine; 2) content of the digital textbook in accordance with the current regulatory framework and practical experience of teachers; 3) techniques of visualisation of educational material in mathematical disciplines and demonstration of some of them in the author's textbooks; 4) the results of the student survey show a strong direct relationship between the rankings of the frequency of use of textbooks in educational activities and their impact on the effective learning process, based on the interpretation of the nine R. Gagné learning events. The developed and implemented author's digital manuals meet the main criteria for their effective functioning: strategic focus, completeness of coverage, intensity, orderliness, coherence and mobility.